A Proposed Theory of Symptom Cluster Management - Jerick Batin Tabudlo (Belitung Raya Foundation, Indonesia, 2021)
Background: Symptom cluster management is in its early stages in many chronic and debilitating illnesses. The development of a proposed theory should be an initial step in advancing this area of interest.Objective: This article presents the development of a Proposed Theory of Symptom Cluster Management.Methods: The concept analysis, statement synthesis, and theory synthesis by Walker and Avant were used in the development of this proposed theory. A search from July to September 2020 for published empirical and theoretical articles was conducted in scientific databases, expanded on the web, and secondary references from identified articles.Results: The Proposed Theory of Symptom Cluster Management is both a descriptive and explanatory theory. The defining characteristics of symptom cluster management include the basic and effectiveness components. Antecedents for symptom cluster management include socio-demographic characteristics, symptom cluster characteristics, individual clinical characteristics, individual illness factors, and situational factors or symptom experience. The consequences are clustered as personal-related, health-related, social-related outcomes, and existential outcomes. Measurement tools for the antecedents and outcomes in symptom cluster management and the analytical and statistical strategies were considered. Relational statements were also identified. Theoretical assertions were advanced.Conclusion: The Proposed Theory of Symptom Cluster Management may provide a holistic approach because it integrates both the symptom cluster and management strategies. The concepts, statements including the complete representation of the proposed theory identified in this article, may provide cues to policymakers and clinical researchers towards the development of tailored interventions and programs.